An Evaluation of the Potential Effectiveness of a Tai Chi Program for Health Promotion Among People with Severe Mental Illness - Ann M. Chapleau D.H.S., OTR/L; Diane Powers Dirette Ph.D., OTL (Scholarworks @ WMU, 2013)
In response to the significant health disparities among persons with severe mental illness (SMI), this pilot study was developed to evaluate the potential effectiveness of a Tai Chi program provided to adults who are members of a psychosocial clubhouse program. A non-randomized, controlled pretest-posttest design was used, and qualitative data from a program evaluation survey is shared tprovide insight into the strengths and limitations of this explorative study. A simplified, beginner-level Tai Chi program was provided twice a week for 12 weeks. Changes in cardiac and pulmonary function and perceived quality of health were measured. Results support the potential for Tai Chi to promote health among this population. Challenges to conducting this type of research are discussed, as well as implications for future, larger studies of health promotioninterventions.